The impact of board qualifications on the complexity of sustainability reports - Merter, Abdullah Kürşat; Balcıoğlu, Yavuz Selim; Çerez, Sedat; Özer, Gökhan (IGI Global, 2024)
The boards of directors serve as an important control unit in the effective management of sustainability reports. Various characteristics, such as the experience and skills of the board members, the presence of female members on the board, and the size of the board, can affect the company's approach to sustainability issues. Therefore, the boards of directors of companies have a critical role in understanding sustainability reports. The objective of this study is to investigate the correlation between the intricacy of sustainability reports and the attributes of the board. For this purpose, firms listed on the Borsa Istanbul (BIST) between 2014 and 2022 were selected as the sample. The complexity of the reports was evaluated on the basis of the length of pages, words, and characters within the reports. The findings indicate a positive relationship between board size, gender diversity within the board, and the length of sustainability reports. Furthermore, it was found that firms with effective audit committees tend to have shorter sustainability reports. © 2025 Elsevier B.V., All rights reserved.
Keywords: Board members; Board size; Boards of directors; Control unit; Effective management; Gender diversity; Istanbul; Sustainability issues; Sustainability report; Word and characters